The circle of fire the great chain of volcanoes and earth faults. - Heintze, Carl. (New York Meredith Press, 1968)
Describes the origin, history, and present day influence of the chain of volcanoes, earth faults, and ocean trenches which rims the Pacific Ocean.
Bibliography: p. 155-156.
Keywords: Volcanoes -- Juvenile literature; Earthquakes -- Juvenile literature; Volcanoes; Earthquakes; Oceanography